Associations Between Food Pantry Size and Foods Received by Clients in Baltimore City (P04-031-19). (13th June 2019) - Ali, Shahmir; Yan, Sally; Gunen, Bengucan; Adams, Lindsay; Gu, Yuxuan; Poirier, Lisa; Craig, Hope; Regan, Tim; Gittelsohn, Joel
Abstract: Objectives: Food pantries act as a supplementary food source for food-insecure households throughout the United States. Recent studies show that healthy food options in food pantries are limited. This may be related to food pantry capacity, suggesting that the size of a food pantry may contribute to the healthfulness of provided foods – an area yet to be studied. Therefore, we aim to examine the relationship between food pantry size and healthfulness of foods received by clients. Methods: We categorized the Maryland Food Bank's Baltimore-based partner food pantries ( n  = 102) as small, medium, or large based on the weight of food they distribute annually. From the pantries who were eligible and interested, we randomly selected 2 small, 2 medium, and 3 large pantries. In terms of food distribution methods, 3 used client-choice and 4 used pre-assembled bags. Food selection data was collected from a total of 74 clients (21 at small, 20 at medium, and 33 at large pantries) between September and October 2018. The Food Assortment Scoring Tool (FAST), a metric used to quantify the nutritional quality of food in pantries, was used to assess the healthfulness of client food bags, with higher scores indicating higher nutritional quality. The Gross Weight Share (GWS) of the food groups described in FAST was calculated to find the proportion of these foods to the total weight of food clients received. Results: There was no statistically significant difference in overall average FAST scores among clients of different sized pantries. However, among client choice pantries, clients of small pantries had FAST scores 9.23 points ( P  = 0.02) higher than clients of medium sized pantries. Small pantries' clients had higher GWS of fresh fruits and vegetables compared to large ( P  = 0.002) and medium pantries ( P  = 0.03), while large pantry clients had higher GWS of sweet and salty snacks than medium pantry clients ( P  = 0.03). Conclusions: Although the average FAST scores across clients from pantries of different sizes did not show statistically significant differences, stratifying FAST scores by food distribution model and examining GWS of key food groups suggest that small food pantry clients receive the largest proportion of healthy foods. These findings suggest the need to prioritize large food pantries in future interventions to help enable clients to receive healthier food products. Funding Sources: Johns Hopkins University Lerner Center for Public Health Promotion.